A Taxonomic Revision of the Genus Hedysarum L. (Fabaceae-Hedysareae) in Iran - Nafisi, Haniyeh; Kazempour‑Osaloo, Shahrokh; Kaveh, Akram; Mahmoodi, Mohammad (Phytotaxa, 2021)
Hedysarum is the second largest genus of the tribe Hedysareae (Fabaceae), in Iran. Considering the rising number of species in Iran, a taxonomic revision of the genus is provided, except for a Hedysarum wrightianum group. As a complementary treatment, a diagnostic key to the species and detailed morphological descriptions are supplied. Based on the reliable molecular phylogeny and morphological evidence in the current study, the taxonomy of some species of H. subsect. Crinifera was re-examined. H. criniferum var. melanotrichum with 1-2 segmented, large, elliptic-semi ovate pods, is raised to the species rank as H. melanotrichum. Also, a new variety of H. atropatanum, (var. glabrum) with pods without setae, is introduced from the type locality. Furthermore, some species were synonymized including H. longipedunculatum with H. fallacinum, H. persicum with H. papillosum, H. orumiehense with H. criniferum, H. bojnordense with H. kopetdaghi, H. elbursense with H. hyrcanum as well as H. kalatense and H. johartchii with H. balchanense. According to the present study, the flora of Iran consists of H. armenium, a representative of H. sect. Hedysarum, and 31 species from H. sect. Multicaulia.